Seks Dalam Perspektif Agama Buddha - Priono, Priono; Ismoyo, Tejo; Pramono, Eko; Poniman, Poniman (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
This study aims to explain the view of sex in the perspective of Buddhism. This research is a descriptive study with a literature review approach using the data obtained in the form of concepts from various general literature on sex that are relevant to the topics discussed. Although sex is genuine based on the natural instincts of all living things. There are different perspectives on sex in every religion. Buddhism also has its own perspective on sex, such as gender and sexual orientation. The results of the research obtained are how a monk and a nun view having sex as something that is considered to violate the rules of monkhood. A Pabbajita is prohibited from having sexual relations because it will result in being expelled from the monkhood.